2005
DOI: 10.1111/j.1368-5031.2005.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation on coexisting of duodenal ulcer and gastric cancer in China

Abstract: The aim of this study was to investigate the prevalence of coexistent duodenal ulcer and gastric cancer in China, then to explore the features of clinical manifestations, endoscopy, pathology and possible pathogenesis. A retrospective analysis has been made on medical records in Remin Hospital, Wuhan University, Hubei Province, China from January 1991 to December 2002. 37 cases of coexistent duodenal ulcer and gastric cancer were found. 24.3% (9/37) had previous history of duodenal ulcer. 81.0% (30/37) of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, in a more recent Swedish study, 206 GC cases developed among 24,456 patients with a DU [2]. Moreover, patients with both GC and a DU are not particularly rare and have been previously reported in Korea (4.8%, 6/126) [23], Taiwan (3.6%, 22/604) [24], and China (1.7%, 37/2132) [9]. In this study, 41 of 541 patients with GC (7.6%) had both GC and a current or a past case of DU, a slightly higher ratio than that found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a more recent Swedish study, 206 GC cases developed among 24,456 patients with a DU [2]. Moreover, patients with both GC and a DU are not particularly rare and have been previously reported in Korea (4.8%, 6/126) [23], Taiwan (3.6%, 22/604) [24], and China (1.7%, 37/2132) [9]. In this study, 41 of 541 patients with GC (7.6%) had both GC and a current or a past case of DU, a slightly higher ratio than that found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, most DUs were at the scar stage (90.2%), which suggests that GC may follow a DU. In previous studies examining GC patients with a DU, most presented with a scar‐stage DU [5,9]. GC is typically a disease of the elderly, whereas DU is a disease of middle age [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The most common complaints of gastric cancer patients are dysphagia, eating restrictions, reflux, and abdominal pain. (4) How to improve quality of life (QOL) has become the focus of gastric cancer research. Clinical researchers are choosing measures of QOL as primary and secondary outcomes in clinical trials.…”
mentioning
confidence: 99%
“…Zhao and coauthors (1) from the Department of Gastroenterology, Remin Hospital of Wuhan University, China have carried out a retrospective analysis of patients with coexisting duodenal ulceration and gastric cancer. The aim of this study was to investigate the prevalence of these coexisting diseases found in the population of this large provincial teaching hospital and to discuss the possible pathogenesis of this infrequent coexistence in a developing country with a high incidence of gastric cancer.…”
mentioning
confidence: 99%